Effect of the microchannel obstacles on the pressure performance and flow behaviors of the hydrogen Knudsen compressor. (23rd August 2019) - Shao, Junda; Ye, Jianjun; Zhang, Yuan; Salem, Shehab; Zhao, Zhenhua; Yu, Jiangcun
Abstract: The hydrogen Knudsen compressor has potential applications on the hydrogen transmission for the microdevices and systems. In this paper, the numerical model of the hydrogen Knudsen compressor was established, combining the NS continuity equations with the slip boundary conditions. The effect of structures on the performance of the hydrogen Knudsen compressor is studied by generating different obstacles in the microchannels. This paper is mainly concerned on the rectangular and the triangular obstacles, and the influence of the obstacles length and height are investigated, respectively. The Knudsen number distribution and the rarefaction of the hydrogen gas flow are analyzed. Also, the characteristic of the pressure increase for the compressor under different parameters are investigated and discussed. The effect of the structure parameters on the flow velocity distributions are detailed described, as well as the velocity contour and the vortex distributions. Moreover, the variation of the Knudsen layers of the hydrogen gas flow in the hydrogen Knudsen compressor is presented, and the key factor of the Knudsen layers is analyzed and discussed. The results is significantly beneficial for the applications and designs of hydrogen Knudsen compressor. Highlights: The increase of the rectangular width is beneficial to the pressure increase. The increase of the triangular height is negative to the pressure increase. The height of obstacles is the key factor for the Knudsen layer.